O perfil ideológico do Manifesto dos Pioneiros da Educação Nova de 1932 a partir de quatro de seus signatários: Fernando de Azevedo, Anísio Teixeira, Lourenço Filho e Paschoal Lemme - Bucholz, Luize Gomes (2020)
In this dissertation, we propose to examine the ideological profile of the 1932 Manifest of Pioneers of New Education, based on four of the 26 of its signatories, namely: Fernando de Azevedo, Anísio Teixeira, Lourenço Filho and Paschoal Lemme. Our objective was to analyze the document in order to investigate whether there were elements of communist ideology in its content or whether it contained only elements of liberal pedagogy. The text was divided into three parts, in the first part we deal with the context of Brazilian education, highlighting the interferences of the Catholic Church and how these interferences reflected in the context of our main focus, in the 1920s and early 1930s. In the second part we analyze the Manifest of 1932 and its proposal for renewal, in addition to highlighting the clashes between Catholic and liberal intellectuals. In the last part of the text, we rely on four of the signatories to the 1932 Manifesto in order to analyze their ideological profile. The methodology used to carry out our work was bibliographic research and for that we rely on the main source in the 1932 Manifest itself, as well as in the works of the authors chosen for analysis, in addition to works by researchers in the area of history of education that contribute with the analysis of the context and with the debate on the theme. From the results of our research, we highlight that the document proposed a school model that had a close resemblance to the pedagogy developed by John Dewey, a liberal intellectual who worked on the democratization of education in the United States. The document presented the attempt to democratize Brazilian education, so it was the most progressive expression in education at the time.